Tenaga Kerja, Tingkat Inflasi, Pendidikan dan Pengangguran Pengaruhnya terhadap Pertumbuhan Ekonomi (Lembaga Penerbitan Unversitas Esa Unggul, 2022)
This study aims to determine whether employment, inflation rates, education, and unemployment can affect economic growth. The independent variables in this study are labor, inflation, education and unemployment, while the dependent variable is economic growth. This study collects data from 10 districts/cities in West Java Province by collecting secondary data from the Central Statistics Agency of West Java Province, with a study period of 7 years (2014 – 2020) and using multiple regression models to test it. The findings of this study indicate that labor, inflation and unemployment have a significant effect on economic growth, while education does not have a significant effect on economic growth. The results of this study can be used by the Regional Government of West Java Province in making policies related to employment, overcoming inflation, policies in the education sector and policies to overcome unemployment, which are expected to be a driving force for increasing economic activity so that it is expected to increase economic growth.